Safety and immunogenicity of conjugate vaccine for typhoid (Vi-DT): Finding from an observer-blind, active-controlled, randomized, non-inferiority, phase III clinical trial among healthy volunteers - Dipesh Tamrakar; Pranodan Poudel; Pragya Thapa; Srijana Singh; Amit Khadgi; Sameera Thapa; Rajendra Tamrakar; Anmol Shrestha; Surendra Madhup; Ganesh Kumar Rai; Birendra Prasad Gupta; Tarun Saluja; et al. (Human Vaccines & Immunotherapeutics)
Typhoid fever is a significant public health concern with most of the sufferers between 15 and 25 y of age in Nepal. We undertook this study to demonstrate Vi polysaccharide conjugated with diphtheria toxoid (Vi-DT) conjugate vaccine which is non-inferior to Typbar typhoid conjugate vaccine, a Vi polysaccharide vaccine conjugated with tetanus toxoid (Vi-TT) with a focus on the adult population from Dhulikhel Hospital which was one of the total four sites in Nepal. In this study, we assigned the eligible participants in 1:1:1:1 ratio by block randomization, and stratified into three age groups (6 months to less than 2 y, 2 y to less than 18 y, and 18 y to 45 y), allotted to Group A, B, C, and D. Group A, B, and C received 25 μg (0.5 mL) of Vi-DT study vaccine and participants in Group D received 25 μg (0.5 mL) Vi-TT vaccine. We descriptively analyzed safety in all the participants receiving one dose of the investigational vaccine. The anti-Vi-IgG seroconversion rate in Vi-DT recipients was 99.71% (97.5% CI 98.04–99.96; 344 of 345 participants) and 99.13% (94.27–99.87; 114 of 115) in Vi-TT recipients which indicates that Vi-DT vaccine is non-inferior to Vi-TT vaccine. In safety aspect, 16.81% of total subject had at least one solicited adverse reaction and 22.61% of the Vi-TT participants experienced at least one solicited adverse reaction with most of them being local adverse reactions. None of the enrolled participants reported serious adverse events. Our study shows that a single dose of the Vi-DT vaccine is immunogenic, safe to administer and non-inferior to the Vi-TT vaccine four weeks after vaccination.